2021
DOI: 10.3390/s21175857
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Serum Spike Protein with Disposable Photonic Biosensors Following SARS-CoV-2 Vaccination

Abstract: While mRNA vaccines have been well-studied in vitro and in animals prior to their use in the human population during the Covid-19 pandemic, their exact mechanisms of inducing immunity are still being elucidated. The large-scale collection of data necessary to fully understand these mechanisms, and their variability across heterogeneous populations, requires rapid diagnostic tests that accurately measure the various biomarkers involved in the immune response following vaccination. Recently, our lab developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 15 publications
(25 reference statements)
1
30
0
Order By: Relevance
“…Furthermore, experimental data show the entrance of the spike protein in cardiac pericytes and pulmonary vascular cells, which promotes cell signaling leading to vascular cell dysfunction and cell growth/hypertrophy [ 28 , 29 ]. It seems extremely interesting to be able to detect spike protein levels in plasma [ 30 , 31 ], but to the best of our knowledge, no practical, clinical use has been implemented thus far while these techniques are not widely available for use to investigate whether there is an association between the observed changes in endothelial function and the spike levels in plasma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, experimental data show the entrance of the spike protein in cardiac pericytes and pulmonary vascular cells, which promotes cell signaling leading to vascular cell dysfunction and cell growth/hypertrophy [ 28 , 29 ]. It seems extremely interesting to be able to detect spike protein levels in plasma [ 30 , 31 ], but to the best of our knowledge, no practical, clinical use has been implemented thus far while these techniques are not widely available for use to investigate whether there is an association between the observed changes in endothelial function and the spike levels in plasma [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…With their platform, the authors investigated serum samples of recently vaccinated test subjects over a time course of 70 days (Figure 19B) [221]. Despite the reported LOD of just 4.2 μg/mL for the spike protein, the observed concentration patterns were in good agreement with data from clinical trials [221]. To conclude this section, two recent reports on fully integrated diagnostic devices are especially recommended to the reader.…”
Section: Photonic Solutions For Longitudinal Monitoring Of Vaccine Ef...mentioning
confidence: 71%
“…Reprinted (adapted) from Ref. [221] with permission of MDPI. A low-cost and portable LIT device for quantitative read-out of Au particles in commercial LFAs (C, left panel) together with bright-field and thermo-photonic amplitude images of test cassettes developed at various IgG concentrations (C, right panel).…”
Section: Photonic Solutions For Longitudinal Monitoring Of Vaccine Ef...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ogata et al, by using a Quanterix assay, found that spike protein levels in the blood of people vaccinated with mRNA-1273 was < 50 pg/mL after vaccination [129] , i.e., several orders of magnitude lower than the levels of spike tested in our study. On the other hand, Cognetti and Miller, by using a Disposable Photonics platform, found that 1-3 days after injection of mRNA vaccine BNT162b2, spike levels underwent an average shift of 15 pm, which corresponds to a maximum concentration of 14.6 μg/mL, returning to a baseline level in less than a month [130] . The discrepancy between the two studies is high and not yet validated.…”
Section: Discussionmentioning
confidence: 99%